The impact of social services activities on students’ communication skills - Muhammad Abdul Mustaqim Salleh; Mohd Adib Abd Muin (Penerbit Universiti Kebangsaan Malaysia, 2024)
This article investigates the impact of social services activities on students' communication skills and focuses on understanding how participation in such activities influences the development of effective communication abilities among students who are involved with uniformed units such as Reserve Officer Training Unit (ROTU), Police Undergraduate Voluntary Corps (SUKSIS), Golfers and Civilian in Universiti Utara Malaysia (UUM). The research adopts a qualitative methods approach which is interviews to collect data from students engaged in various social services. All of them become a holistic student when they can mix all the skills like communication and get involved in social services to give the best performances to their Inapan Siswa (INASIS) and have a perfect combination of skills added to the Islamic perspective which can attract other students to get involved in any social services. The study investigates the extent and nature of student's involvement in various social services activities, considering both voluntary and organized initiatives, and to emphasize the importance of holistic student development by showcasing the role of social services activities in fostering not only academic excellence but also essential interpersonal skills crucial for personal and professional success, encompassing verbal, non-verbal, and interpersonal aspects. In conclusion, this finding contributes to the understanding of the positive influence of social services activities on students' communication competencies.